Fermentation of pomegranate matrices with Hanseniaspora valbyensis to produce a novel food ingredient. (15th April 2023) - Limongelli, Rosangela; Minervini, Fabio; Calasso, Maria
Abstract: We aimed to develop a large-scale consumption food, added with fermented pomegranate matrices, to be able to meet consumer's needs. Chemical composition, antioxidant activity, and microbiota of pomegranate were analysed. Yeasts dominated (ca. 5 log cfu/g) the matrices. Among four Hanseniaspora valbyensis strains able to ferment pomegranate, S-L1 caused the highest increase in mineral in seeds (e.g., 162 mg of K/100 g of fermented seeds vs. 104 mg of K/100 g of unfermented seeds). Then, we designed a granola snack supplemented with pomegranate seeds flour (PSF) and compared: G-FS, granola containing fermented PSF; G-US, supplemented with unprocessed PSF; G-C, conventional granola. Compared to G-C, the use of PSF increased antioxidant activity of the snack (ca. 60% DPPH∙ scavenging activity vs. ca. 40% activity of G-C). The highest contents of minerals were expected in G-FS and G-C, compared to G-US, while lower energetic values were expected for the two fortified snacks. Fermentation of seeds with H. valbyensis S-L1 also improved acceptability of fortified snack (score on 1–9 scale: 6.3), making it more similar to the control (7.5) and more appreciated than G-US (4.9). The results could intrigue industries searching for novel foods, with improved nutritional quality and sustainability. Highlights: Yeasts are predominant in pomegranate microbiota. Hanseniaspora valbyensis was a suitable starter for pomegranate seeds fermentation. The fermented pomegranate seeds improved sensory features of granola snacks. The fermented pomegranate seeds improved antioxidant activity of granola.